THE FEEDBACK ELABORATION AND ITS IMPLICATIONS TOWARDS INDONESIAN SUBJECT - Jefri Kamil; Yusmarwati Binti Yusof; Atmadinata Atmadinata; Said Nuwrun; Alpino Susanto (Universitas Putera Batam, 2019)
Learning Indonesian as a school subject can be intended as an effort to develop Indonesian language functions for Senior High School students to obtain information, control behavior, interact with others, express personal feelings or intentions, develop learning skills, and use language to convey information. To achieve this purpose, the teacher must do learning optimally. This paper aims to elaborate on the various phenomena of learning Indonesian in Senior High school and various references as the basis of language and conclusions. The elaboration feedback strategy is the focus of this paper and intended as a discourse and input for the teacher as the person in charge of learning process in the classroom.